10 workshops on Immunology of preeclampsia. (September 2017) - Gerard, Chaouat
Highlights: This paper surveys the evolution of concepts from the primpaternity proposal (Robillard) to the multi stage theory (Redman) Abstract: For the 10th issue of the « island workshops », now the Reunion Workshops, organised by Pierre Yves Robillard since the first one in Tahiti challenging the "vascular disease only" theory of pre eclampsia and introducing the primipaternity concept, we examined the reasons for considering an Immunological approach to the disease. This (brief) overview thus examines several important topics in an Immunological framework. I have chosen to present here the evolution of the main themes rather than a purely chronological vision.